Pathogenic Gene Mutations or Variants Identified by Targeted Gene Sequencing in Adults With Hemophagocytic Lymphohistiocytosis - Miao, Yi; Zhu, Hua-Yuan; Qiao, Chun; Xia, Yi; Kong, Yiling; Zou, Yi-Xin; Miao, Yu-Qing; Chen, Xiao; Cao, Lei; Wu, Wei; Liang, Jin-Hua; Wu, Jia-Zhu; et al. (Frontiers in Immunology, 2019)
Hemophagocytic lymphohistiocytosis (HLH) can be classified into primary HLH and secondary HLH. Primary HLH usually occurs in infants and children with an underlying genetic defect, and there are also teens and occasional adults with primary HLH. Most cases with secondary HLH are adult patients with secondary triggers including infections, malignancies, and autoimmune diseases. The distinction between primary HLH and secondary HLH seems to be less straightforward, as patients with secondary HLH may also have genetic defects while primary HLH can be triggered by secondary causes. In this study, using amplicon-based targeted gene sequencing (TGS), we sequenced eighteen HLH-related genes in 112 adult HLH cases, which were mostly secondary HLH. Mutations or rare variants were identified in 48 cases (42.9%). All the variants except one were missense variants, and biallelic gene mutations were identified in 3 cases in which only one case harbored homogenous missense mutation. Recurrent variants including UNC13D p.G863D and AP3B1 p.T359A are much more prevalent in our cohort than in normal East Asian population, and in silico analysis predicted pathogenicity of these variants. In conclusion, according to our study, genetic defects may also contribute to the development of adult HLH cases or secondary HLH cases.